The Relationship between Entrepreneurship and Shadow Economy: A Cross-Country Study - Dan-Andrei COCA; Carmen NASTASE (Communications of International Proceedings, 2021)
This study examines the relationship between shadow economy and entrepreneurship, with the main objective of establishing whether there is a quantifiable correlation between the two and in order to test previous research results that found the informal economy as having a negative effect on entrepreneurship. Such relationship was quite heavily researched in the last few years, as revealed by the co-occurrence network of terms’ map, generated using VOSviewer – a computer program that was developed for constructing and viewing bibliometric maps. In this context, we test whether there is less entrepreneurial activity in economies where shadow economy is larger and if a larger shadow economy can be linked to higher levels of enterprises deaths. The research is carried on a cross-country data for the 28 EU Member States and it uses IBM SPSS Statistics 20 in order to analyze and interpret the results. The main finding was that, there is no statistically significant linear relationship between the data. However, the direction of the relationship between shadow economy and business growth is negative and the relationship between the shadow economy and the enterprise death rate is positive, meaning that the variables tend to increase together. This leads to the conclusion that part of the enterprises that exit the official economy can actually be found to move to the informal sector. Such assumption will be researched in future studies.
Keywords: Entrepreneurship; European Union; Shadow Economy; Informal Entrepreneurship.